If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + 3 = 3(6x + -4) Reorder the terms: 3 + 18x = 3(6x + -4) Reorder the terms: 3 + 18x = 3(-4 + 6x) 3 + 18x = (-4 * 3 + 6x * 3) 3 + 18x = (-12 + 18x) Add '-18x' to each side of the equation. 3 + 18x + -18x = -12 + 18x + -18x Combine like terms: 18x + -18x = 0 3 + 0 = -12 + 18x + -18x 3 = -12 + 18x + -18x Combine like terms: 18x + -18x = 0 3 = -12 + 0 3 = -12 Solving 3 = -12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 54.7=-9.3+8.2 | | x^5=31 | | 7x-8=9x+7 | | 15+2(4x-1)=18-(4x-7) | | 0.5x*x=8 | | 9-2(2x+4)=4x+5(x-5) | | 2x=4-7 | | (-14x+18)+(-6x+2)=180 | | 70=-8x-98-4x | | 2(y-4)=5(y+1)-7 | | 2.1(2.3+2.1x)=11.65+x | | 6c^2+11c+3=0 | | 9x+8y=0 | | mp+mn=t | | 13-5r-14=8r+13-6r | | 2x(4-22)= | | 4f^2+11f-3=0 | | 6y+10=-4y-10 | | 3w^2-17w-6=0 | | 8y-6-3y+5=0 | | 0.5x+0.7=-0.75 | | 15x^2-27x-6= | | -6(3n+5)=20 | | 5n+18-3n=38 | | -x(3+4)= | | 3p=8p-55 | | 12(2x-9)=3(8x+8) | | 10x^2-24x+18-2y=0 | | (x+3)(x-2)=6 | | 3p-9=2p+12 | | -6(7x-1)=-42x-6 | | J+4=-15 |